2017
DOI: 10.1371/journal.pone.0176179
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale modifications in the early heating stages of bone are heterogeneous at the microstructural scale

Abstract: Nanoscale studies of bone provide key indicators to evidence subtle structural changes that may occur in the biomedical, forensic and archaeological contexts. One specific problem encountered in all those disciplines, for which the identification of nanostructural cues could prove useful, is to properly monitor the effect of heating on bone tissue. In particular, the mechanisms at work at the onset of heating are still relatively unclear. Using a multiscale approach combining Raman microspectroscopy, transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Also, differences in the post-processing of the spectra could also affect the sensitivity to thermal-related changes in RS properties of bone. Lastly, using X-ray diffraction techniques, Gourrier and colleagues (40) also found that the thickness of mineral crystals increased as the heating temperature increased, and this ultrastructural change may have translated to the higher crystallinity by RS observed in the present study. How such a change affects bound water is unknown.…”
Section: Discussionsupporting
confidence: 69%
“…Also, differences in the post-processing of the spectra could also affect the sensitivity to thermal-related changes in RS properties of bone. Lastly, using X-ray diffraction techniques, Gourrier and colleagues (40) also found that the thickness of mineral crystals increased as the heating temperature increased, and this ultrastructural change may have translated to the higher crystallinity by RS observed in the present study. How such a change affects bound water is unknown.…”
Section: Discussionsupporting
confidence: 69%
“…Most X-ray studies concluded an absence of mineral crystal structure modifications before 400 °C, while a rapid crystal growth has been reported at ~ 750 °C [18][19][20]. In a recent study we provided evidence that the mineral nanocrystals increase in size and become more disorganized at temperatures as low as 100 °C [21]. In addition, many debates remain open concerning the nature of a postulated high temperature phase transition, the coexistence of different crystallographic phases, as well as the presence of ionic defects above and below the critical temperature of Tcr = 750 °C [22].…”
Section: Introductionmentioning
confidence: 83%
“…As Thompson et al () stated previously, it is possibly related with differences in bone structure and bone remodeling, which have been found between trabecular and compact bone (Reznikov et al, ). Intrabone heterogeneity in histological tissue has also been identified as a cause for heat‐induced nanoscale differences in the variance of particle thicknesses (Gourrier et al, ). In particular, Gourrier et al () detected differences in the nanoscale properties of osteonal vs interstitial tissue and fibrous vs fibrolamellar tissue.…”
Section: Discussionmentioning
confidence: 99%
“…When present, all of the long bones, metacarpals, metatarsals, and tarsals from both left and right sides of each skeleton were used (Table ). Human bones are quite variable in terms of structure, shape and size, and such variables may in some way interfere with bone parameters, especially with crystallinity (Reznikov, Chase, Brumfeld, Shahar, & Weiner, ; Gourrier et al, ). Therefore, three different bone types were investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation